FATWA ALIRAN SESAT DAN POLITIK HUKUM MAJELIS ULAMA INDONESIA (MUI) - Hasyim, Syafiq (Al-Ahkam, 2015)
MUI (The Indonesian Council of Ulama) is an institution established by the government of Indonesia that one of its functions is to formulate religious fatwas. The existence of the MUI as the representatives of various religious organizations, and therefore claimed to be the big tent of Muslims, became the basis for the existence of these functions. Nevertheless MUI’s fatwas on religious denominations in Indonesia, is considered partly responsible for the occurrence of discriminatory behavior and violence based on religion. This article would like to see the political aspects of the law on the MUI’s fatwas about the deviant groups which is considered as a barrier of religous freedom in Indonesia and at the same time as the trigger acts of violence based on religion. MUI’s fatwas about the deviant groups can be analyzed in at least two approaches. First, in the perspective of the discourse of blasphemy, and second from the perspective of the discourse of legal pluralism, institutionalizing MUI, and theology.